Mother’s Perception of Obesity with Overweight and Obesity in Children Aged 7-12 Years at Kabupaten Aceh Barat - Sri Wahyuni Muhsin, S.Si., MPH.; Emy Huriyati; Leny Latifah; Rinawati Rinawati (Journal of Nutrition Science, 2022)
Nutrition problems in Indonesia are already classified as multiple nutritional problems, not just nutritional deficiency problems, but the prevalence of overweight and obesity also increases. In 2010 the prevalence of overweight and obesity in Aceh province was 11.2 percent and in 2013 was 14.8 percent resulting in an increase of 3.6 percent. Mother's perception is one factot that can cause cause overweight and obesity. This study wanted to analyze the factors This study wanted to analyze the factors of mother perception in children aged 7-12 years become the cause of overweight and obesity. This study was an observational analytic study with cross sectional design aimed at assessing relationship of mother's perception on obesity-related weight status in first-fifth grade elementary school children aged 7-12 years at Kabupaten Aceh Barat. The sample size is 289 students. Determination of child obesity status using Body Mass Index based on Age (IMT/U), that is overweight and obesity if IMT/U>1.0 SD. Data of mother's perception were obtained through questionnaire. There are 51.90% of 289 respondents who had overweight and obesity. There is no relationship between mother perception of obesity with overweight and obesity (p=0.426). But it is different when viewed specifically about the mother's perception related to the child's weight status. Wrong mother's perception of child's weight status has a risk of 4.15 times greater than the right one. There is a correlation between mother’s perception of child's weight status with overweight and obesity.